HILBERT SPACE IN SEQUENCE SPACE l2 - Alwi, Wahidah (Jurusan Matematika FST-UIN Alauddi Makassar, 2014)
The main object of the vectors are the vectors can be added together and generate a vector, and produces a number is multiplied by another vector. Any set of objects with properties like this are called